Lytic Bacteriophage EFA1 Modulates HCT116 Colon Cancer Cell Growth and Upregulates ROS Production in an Enterococcus faecalis Co-culture System - Kabwe, Mwila; Meehan-Andrews, Terri; Ku, Heng; Petrovski, Steve; Batinovic, Steven; Chan, Hiu Tat; Tucci, Joseph (Frontiers in Microbiology, 2021)
Enterococcus faecalis is an opportunistic pathogen in the gut microbiota that’s associated with a range of difficult to treat nosocomial infections. It is also known to be associated with some colorectal cancers. Its resistance to a range of antibiotics and capacity to form biofilms increase its virulence. Unlike antibiotics, bacteriophages are capable of disrupting biofilms which are key in the pathogenesis of diseases such as UTIs and some cancers. In this study, bacteriophage EFA1, lytic against E. faecalis, was isolated and its genome fully sequenced and analysed in silico. Electron microscopy images revealed EFA1 to be a Siphovirus. The bacteriophage was functionally assessed and shown to disrupt E. faecalis biofilms as well as modulate the growth stimulatory effects of E. faecalis in a HCT116 colon cancer cell co-culture system, possibly via the effects of ROS. The potential exists for further testing of bacteriophage EFA1 in these systems as well as in-vivo models.